2020
DOI: 10.3390/molecules25163563
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effect of 3-Hydroxy-β-Ionone Identified from Moringa oleifera Lam. Leaf on Human Squamous Cell Carcinoma 15 Cell Line

Abstract: Squamous cell carcinoma is the most common type of head and neck cancer worldwide. Radiation and chemotherapy are general treatments for patients; however, these remedies can have adverse side effects and tumours develop drug resistance. Effective treatments still require improvement for cancer patients. Here, we investigated the anti-cancer effect of Moringa oleifera (MO) Lam. leaf extracts and their fractions, 3-hydroxy-β-ionone on SCC15 cell line. SCC15 were treated with and without MO leaf extracts and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…In addition, it caused apoptosis and cell cycle arrest at G2/M phase in these cells. Apoptosis was indicated by an increase in cleaved caspases and Bax with a decrease in Bcl-2 (as seen with β-ionone, Figure 3 ) [ 121 ]. It appears that 3-hydroxy-β-ionone is produced endogenously from BCO2 asymmetric cleavage of zeaxanthin, a carotenoid with a 3-hydroxy-β-ionone ring [ 40 ].…”
Section: Ionone Effectsmentioning
confidence: 99%
“…In addition, it caused apoptosis and cell cycle arrest at G2/M phase in these cells. Apoptosis was indicated by an increase in cleaved caspases and Bax with a decrease in Bcl-2 (as seen with β-ionone, Figure 3 ) [ 121 ]. It appears that 3-hydroxy-β-ionone is produced endogenously from BCO2 asymmetric cleavage of zeaxanthin, a carotenoid with a 3-hydroxy-β-ionone ring [ 40 ].…”
Section: Ionone Effectsmentioning
confidence: 99%
“…49 In addition, 1 was recently isolated from the leaves of Moringa oleifera and found to inhibit proliferation of a squamous cell carcinoma cell line. 50 Besides the apocarotenoids, the 1 H NMR spectrum of fraction D (data not shown) indicated the presence of a carotenoid, 51 which was initially inferred to be zeaxanthin (4) based on previous reports that spirulina is an abundant source of zeaxanthin. 52 To confirm this assumption, high-resolution LC-MS/MS was performed on the crude spirulina extract and a USP Reference Standard, Aztec Marigold Zeaxanthin Extract.…”
Section: ■ Materials and Methodsmentioning
confidence: 93%
“…The anti-carcinogenic potential of aqueous extract of M. oleifera (AEMO) in vitro and in vivo was studied and revealed that AEMO treatment did not induce significant alterations of liver and kidney function and haematological parameters. 21 The research by Luetragoon et al 22 found that the extract of M. oleifera leaf can up-regulate cysteine, downregulate the anti-apoptotic factors, and induce apoptosis of cancer cells. The treatment using the methanolic extracts of Moringa oleifera leaves (MOME) induced apoptosis with G2/M enrichment in breast cancer cells, thus enhance the immunological potential of M. oleifera.…”
Section: Discussionmentioning
confidence: 99%